Some surprising facts about working time accounts and the business cycle - Balleer, Almut; Gehrke, Britta; Merkl, Christian (Bonn, 2015)
"Working time accounts (WTAs) allow firms to smooth hours worked over time. This paper analyzes whether this increase in flexibility has also affected how firms adjust employment in Germany. Using a rich microeconomic dataset, we show that firms with WTAs show a similar separation and hiring behavior in response to revenue changes as firms without WTAs. One possible explanation is that firms without WTAs used short-time work instead to adjust hours worked. However, we find that firms with WTAs use short-time work more than firms without WTAs. These findings call into question the popular hypothesis that WTAs were the key driver of the unusually small increase in German unemployment in the Great Recession."